Normal DNA methylation status in sperm from a somatic cell cloned bull and their fertilized embryos. (31st July 2018) - Yamanaka, Ken‐Ichi; Yamashita, Kyoko; Khatun, Hafiza; Wada, Yasuhiko; Tatemoto, Hideki; Sakatani, Miki; Takenouchi, Naoki; Takahashi, Masashi; Watanabe, Shinya
Abstract: Epigenetic reprogramming confers totipotency even during somatic cell nuclear transfer (SCNT), which has been used to clone various animal species. However, as even apparently healthy cloned animals sometimes have aberrant epigenetic status, the harmful effects of these defects could be passed onto their offspring. This is one of the biggest obstacles for the application of cloned animals for livestock production. Here, we investigated the DNA methylation status of four developmentally regulated genes ( PEG3, XIST, OCT4, and NANOG ) in sperms from a cloned and a non‐cloned bull, and blastocysts obtained by in vitro fertilization using those sperms and SCNT. We found no differences in the methylation status of the above genes between cloned and non‐cloned bull sperms. Moreover, the methylation status was also similar in blastocysts obtained with cloned and non‐cloned bull sperms. In contrast, the methylation status was compromised in the SCNT blastocysts. These results indicate that sperm from cloned bulls would be adequately reprogrammed during spermatogenesis and, thus, could be used to produce epigenetically normal embryos. This study highlights the normality of cloned bull offspring and supports the application of cloned cattle for calf production.